CORRELATION AND PATH ANALYSIS IN AFRICAN MARIGOLD (TAGETES ERECTA L.) - T. USHA BHARATHI; M. JAWAHARLAL; M. KANNAN; N. MANIVANNAN (The Bioscan, 2014)
A study was undertaken to determine association between different quantitative traits of 28 genotypes of African marigold collected from various sources. The positive and significant correlation was recorded for flower yield per plant with plant height (0.64), stem girth (0.60), number of flowers per plant (0.53), flower size (0.70), single flower weight (0.69) and number of petals per flower (0.52). The results of path analysis indicated that total duration (0.77), number of flowers per plant (0.56), flower size (0.51), single flower weight (0.38) and number of harvest per plant (0.21) had maximum direct effect. This result suggests that these traits can be directly used to improve the yield of African marigold.